Overview of Patent Protection in Public Services Towards Smart City: Case Study in Yogyakarta - Budi Agus Riswandi; Chrisna Bagus Edhita Praja (Varia Justicia, 2021)
In Indonesia, the smart city idea strives to improve public services by combining a variety of components like as governance, economy, quality of life, environment, human resources, and transportation. These developments are mirrored in public service applications such as population administration, e-mobile ID cards, non-cash parking retribution, and smart retribution. However, such applications acquire no special protection. The purpose of this study is to define patent protection as an instrument for directing the development of public services toward becoming a smart city in Yogyakarta, Indonesia . This study employs a method of normative juridical legal research in conjunction with qualitative descriptive data analysis. The findings indicate that while the city of Yogyakarta develops android-based public service applications as a method of transforming public services, this innovation lacks legal protection as a means of controlling the application. Patent instruments can be utilized to protect android-based public service applications through the implementation of the Patent Law. The use of this Patent Law has had no effect on efforts to reproduce the Android-based public service application in other domains.